Characteristics of the population of an excellence center in healthcare for the elderly - Figueiredo, Vitória Rodrigues; da Silva, Midiã Gomes; de Oliveira, Conceição Maria; Bonfim, Cristine Vieira do (Revista de Enfermagem UFPE on line, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> ABSTRACT Objective: describing the sociodemographic characteristics, functional capacity and cognitive profile of the elderly who are users of a clinic of an excellence center for healthcare of the elderly (CRASPI). Method: cross-sectional study by means of documental analysis of 110 elderly who receive care from CRASPI, in Recife/PE/Brazil. These users’ medical files were surveyed to obtain sociodemographic variables and scores for daily life activities of (DLAs) and the Mini-Mental State Examination (MMSE). Was used descriptive statistics (mean, median, standard deviation and frequency distribution). The research project was approved by the Research Ethics Committee of the Oswaldo Cruz University Hospital/Emergency Hospital of Pernambuco, CAEE 0100.0.106.000-11. Results: most of these elderly individuals were females (72.73%), aged 70 to 79 years (47.62%) and widowed (41.35%), and had completed their elementary education (47.71%). Conclusion: these results provide knowledge about the population that is cared at CRASPI, thus contributing towards planning actions for disease prevention and health promotion among the elderly people. Descriptors: Aged; Health Profile; Demographic Aging; Health of the Elderly; Health Services for the Aged. RESUMO Objetivo: descrever as características sociodemográficas, a capacidade funcional e o perfil cognitivo dos idosos usuários do ambulatório de um Centro de Referência em Atendimento à Saúde da Pessoa Idosa (Craspi). Método: estudo descritivo de coorte transversal, com análise documental nos prontuários de 110 idosos usuários de um Craspi, no Recife/PE/Brasil. Foi empregada a estatística descritiva (média, mediana, desvio-padrão e distribuição de frequências). O projeto de pesquisa foi aprovado pelo Comitê de Ética em Pesquisa do Hospital Universitário Oswaldo Cruz/Pronto Socorro Cardiológico de Pernambuco, CAEE 0100.0.106.000-11. Resultados: a maior parte dos idosos é do sexo feminino (72,73%), na faixa etária dos 70 a 79 anos (47,62%), viúvos (41,35%) e tinham o primeiro grau (47,71%). Conclusão: esses resultados propiciam um conhecimento sobre a população que é atendida no Craspi, contribuindo com o planejamento das ações de prevenção de morbidades e na promoção de saúde dos idosos. Descritores: Idoso; Perfil Epidemiológico; Envelhecimento da População; Saúde do Idoso; Serviços de Saúde para Idosos. RESUMEN Objetivo: describir las características sociodemográficas, la capacidad funcional y el perfil cognitivo de los ancianos usuarios del ambulatorio de un Centro de Referencia en Atención Sanitaria del Anciano (CRASPI). Método: se trata de un estudio de corte transversalrealizada a través del análisis documental de los prontuarios de 110 ancianos do CRASPI, situado en Recife/PE/Brasil. Se utilizó estadística descriptiva (media, mediana, desviación estándar y distribución de frecuencia). El proyecto de investigación fue aprobado por el Comité Ético de Investigación del Hospital Universitario Oswaldo Cruz/Emergency Hospital de Pernambuco (CAEE 0100.0.106.000-11). Resultado: la mayor parte de los ancianos es del sexo femenino (72,73%), con edades entre los 70 y los 79 años (47,62%), viudos (41,35%) y tenían enseñanza primaria (47,71%). Conclusión: estos resultados propician un conocimiento sobre la población que atiende el CRASPI, contribuyendo con la planificación de las acciones de prevención de morbilidad y en el fomento de la salud de los ancianos. Descriptores: Anciano; Perfil de Salud, Envejecimiento de Lapoblación; Salud del Anciano; Servicios de Salud para Ancianos.